2005
DOI: 10.1021/jp047376+
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Process of Adsorption of Alkanes and Alkenes on Zeolites

Abstract: The adsorption of alkanes and alkenes on zeolites is investigated by comparing the adsorption characteristics for three types of zeolite: ferrierite, ZSM-5, and mordenite. The activation energy for the diffusion of propane and n-butane on ferrierite and the heat of adsorption of C 2 -C 4 alkanes and alkenes on zeolites and silica are estimated based on Fourier transform infrared spectroscopy, and the diffusion processes in the micropores are elucidated by comparing the results with previously reported activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 34 publications
7
64
0
1
Order By: Relevance
“…[ [36][37][38] The elastic incoherent scattering function (EISF) allows the intensity of the individual quasi-elastic components to be compared with the elastic component (Figure 8). The EISF for the component corresponding to jump diffusion of free ethanol (Figure 8a), decreases at higher temperatures, showing an increase in the relative intensity of this component with respect to the elastic component.…”
Section: Quasi-elastic Neutron Scattering Of Ethanol and Ethermentioning
confidence: 99%
“…[ [36][37][38] The elastic incoherent scattering function (EISF) allows the intensity of the individual quasi-elastic components to be compared with the elastic component (Figure 8). The EISF for the component corresponding to jump diffusion of free ethanol (Figure 8a), decreases at higher temperatures, showing an increase in the relative intensity of this component with respect to the elastic component.…”
Section: Quasi-elastic Neutron Scattering Of Ethanol and Ethermentioning
confidence: 99%
“…For butenes some NMR and infrared based adsorption studies are available. The adsorption of butenes on H-ZSM-5 and mordenite was experimentally investigated by Domen et al [12,13,[17][18][19]. On H-ZSM-5, they observed that at sub-ambient temperatures a stable p-complex was formed and that double bond isomerization occurred already at 230 K [13,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, experimental investigations in molecular details of structures and adsorption dynamics and interaction energies of hydrocarbons in zeolites have been reported [12][13][14][15][16][17][18]. It was found that the pore size of zeolites had strong effects on the geometries of adsorption sites, the structures of the adsorption complexes, and the adsorption energies.…”
Section: Introductionmentioning
confidence: 99%
“…The linear correlations of interaction energy (heat of adsorption) and the number of carbon atoms of n-alkanes have been found in various zeolites [19]. However, the adsorption of alkenes in acidic zeolites is complicated by the rapid reactions of oligomerization and isomerization at the Brønsted acid sites [17,18,20]. The heat of adsorption of alkenes cannot be experimentally measured because of these reactions.…”
Section: Introductionmentioning
confidence: 99%